Ghibah in Islam: Meaning, Consequences, and Explanation of the Hadith “Ghibah is Worse than Zina” - Sofyan, Nur Baety (El-Sunan: Journal of Hadith and Religious Studies, 2025)
This study aims to present a clear interpretation of the Ghibah (backbiting) from Islamic perspective, the verses indicating its prohibition, Causes and their treatment, how the repentance of the backbiter (At- Taubah), and the explanation of the hadith “ghibah (backbiting) is worse than zina (adultery)”. This research uses the library research method with a descriptive analytical approach, which involves collecting data,  considering Muslim scholar`s views and explanation of the hadith “ghibah (backbiting) is worse than zina (adultery)”.  The study begins by explaining the definition of Ghibah from Islamic perspective, indicating verses of its prohibition, answering the question that “Is it permissible to listen to backbiting?” followed by causes of backbiting and how their treatment, the repentance of the backbiter (tawbah of the one who backbit others), and the explanation of the hadith “ghibah (backbiting) is worse than zina (adultery)”. The results of this study can be summarized into three main points: First: From several opinions of scholars which according to researchers can representative describing the definition of ghibah, it is as according to Imam Al-Ghazali that ghibah or backbiting as mentioning your sibling in a way he would not appreciate, even verbal backbiting concerning his appearance, family, personality, deeds, words, faith and life, alongside his garments, residence and mount.  Second: Some common causes of backbiting are relieving anger, agreeing with peers and pleasing companions, the desire to elevate oneself by belittling others, joking and mockery, envy (hasad), deflecting blame or justifying oneself, excess free time and boredom, and seeking favor with superiors. Third: The hadith stating: “Backbiting is worse than adultery”, it is clear that the narration is extremely weak (da‘īf jiddan) or even fabricated (mawḍū‘), according to several well-known hadith scholars. The hadith should not be used as evidence in legal or theological rulings due to its weakness, its message aligns with Islamic moral values. It reminds believers to control their speech, seek sincere repentance, and strive to avoid sins—especially those that harm others.